Immunomodulatory Role of Capsular Polysaccharides Constituents of Cryptococcus neoformans - Decote-Ricardo, Debora; LaRocque-de-Freitas, Isabel Ferreira; Rocha, Juliana Dutra B.; Nascimento, Danielle O.; Nunes, Marise P.; Morrot, Alexandre; Freire-de-Lima, Leonardo; Previato, Jose Osvaldo; Mendonça-Previato, Lucia; Freire-de-Lima, Celio Geraldo (Frontiers in Medicine, 2019)
Cryptococcosis is a systemic fungal infection caused by Cryptococcus neoformans. In immunocompetent patients, cryptococcal infection is often confined to the lungs. In immunocompromised individuals, C. neoformans may cause life-threatening illness, either from novel exposure or through reactivation of a previously acquired latent infection. For example, cryptococcal meningitis is a severe clinical disease that can manifest in people that are immunocompromised due to AIDS. The major constituents of the Cryptococcus polysaccharide capsule, glucuronoxylomannan (GXM) and galactoxylomannan (GalXM), also known as glucuronoxylomanogalactan (GXMGal), are considered the primary virulence factors of Cryptococcus. Despite the predominance of GXM in the polysaccharide capsule, GalXM has more robust immunomodulatory effects on host cellular immunity. This review summarizes current knowledge regarding host-Crytococcus neoformans interactions and the role of capsular polysaccharides in host immunomodulation. Future studies will likely facilitate a better understanding of the mechanisms involved in antigenic recognition and host immune response to C. neoformans and lead to the development of new therapeutic pathways for cryptococcal infection.